Physical, thermal, and antibacterial effects of active essential oils with potential for biomedical applications loaded onto cellulose acetate/polycaprolactone wet-spun microfibers - Felgueiras, Helena Prado (2020)
New approaches to deal with the growing concern associated with antibiotic-resistant bacteria are emerging daily. Essential oils (EOs) are natural antimicrobial substances with great potential to mitigate this situation. However, their volatile nature, in their liquid-free form, has restricted their generalized application in biomedicine. Here, we propose the use of cellulose acetate (CA)/polycaprolactone (PCL) wet-spun fibers as potential delivery platforms of selected EOs to fight infections caused by Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). Twenty EOs were selected and screened for their minimal inhibitory concentration (MIC), using the antibiotic ampicillin as positive control. The cinnamon leaf oil (CLO), cajeput oil (CJO), and the clove oil (CO) were the most effective EOs, against the Gram-positive (MIC < 22.38 mg/mL) and the Gram-negative (MIC < 11.19 mg/mL) bacteria. Uniform microfibers were successfully wet-spun from CA/PCL with an averaged diameter of 53.9 ± 4.5 µm, and then modified by immersion with CLO, CJO and CO at 2 × MIC value. EOs incorporation was confirmed by UV-visible spectroscopy, Fourier-transformed infrared spectroscopy, and thermal gravimetric analysis. However, while microfibers contained ampicillin at MIC (control) after the 72 h modification, the CLO, CO and CJO-loaded fibers registered ≈ 14%, 66%, and 76% of their MIC value, respectively. Data showed that even at small amounts the EO-modified microfibers were effective against the tested bacteria, both by killing bacteria more quickly or by disrupting more easily their cytoplasmic membrane than ampicillin. Considering the amount immobilized, CLO-modified fibers were deemed the most effective from the EOs group. These results indicate that CA/PCL microfibers loaded with EOs can be easily produced with increased antibacterial action, envisioning their use as scaffolding materials for the treatment of infections.